Study on Supply Chain considering Anticipated Regret under Price Discount. (12th October 2020) - Zhang, Nian; Li, Bin
Abstract : The aim of this study is to research the impact of consumer regrets on the supply chain caused by the company's "discount promotion." This paper introduces the theory of anticipated regret and price discount into the supply chain. By quoting the negative utility formula of consumers' anticipated regret under price discount, it quantitatively describes the demand function of the original product and the discount product. The model under centralized and decentralized decision making is constructed, and revenue-sharing contract is adopted to coordinate the supply chain. The conclusions are as follows. (1) Affected by the anticipated regret under the price discount, the price of the product increases first and then decreases with the regret sensitivity coefficient and consumer heterogeneity sensitivity increases. In addition, the price under the leadership structure of the manufacturer is the highest. (2) Price discounts enhance consumers' perception of anticipated regret. Under the stimulation of price discounts, the price of products increases first and then decreases. (3) The revenue-sharing contract could not coordinate the supply chain, and the introduction of a profit-sharing mechanism is achieved the Pareto improvement of the supply chain.